Intrinsic Properties of Macroscopically Tuned Gallium Nitride Single‐Crystalline Facets for Electrocatalytic Hydrogen Evolution. Issue 44 (8th July 2019) - Hu, Haixiao; Chang, Bin; Sun, Xiucai; Huo, Qin; Zhang, Baoguo; Li, Yanlu; Shao, Yongliang; Zhang, Lei; Wu, Yongzhong; Hao, Xiaopeng
Abstract: The anisotropy of crystalline materials results in different physical and chemical properties on different facets, which warrants an in‐depth investigation. Macroscopically facet‐tuned, high‐purity gallium nitride (GaN) single crystals were synthesised and machined, and the electrocatalytic hydrogen evolution reaction (HER) was used as the model reaction to show the differences among the facets. DFT calculations revealed that the Ga and N sites of GaN (100) had a considerably smaller Δ G H* value than those of the metal Ga site of GaN (001) or N site of GaN (00−1), thereby indicating that GaN (100) should be more catalytically active for the HER on account of its nonpolar facet. Subsequent experiments testified that the electrocatalytic performance of GaN (100) was considerably more efficient than that of other facets for both acidic and alkaline HERs. Moreover, the GaN crystal with a preferentially (100) active facet had an excellently durable alkaline electrocatalytic HER for more than 10 days. This work provides fundamental insights into the exploration of the intrinsic properties of materials and designing advanced materials for physicochemical applications. Abstract : Showing a different side : The anisotropy of crystalline materials results in different physical and chemical properties on different facets. The intrinsic electrochemical properties of different facets of a gallium nitride (GaN) single‐crystal material have been investigated by means of macroscopic facet tuning (see figure).